2018
DOI: 10.3892/mmr.2018.8826
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of peroxiredoxin V increases glutamate‑induced apoptosis in HT22 hippocampal neuron cells

Abstract: High concentrations of glutamate may mediate neuronal cell apoptosis by increasing intracellular reactive oxygen species (ROS) levels. Peroxiredoxin V (Prx V), a member of the Prx family, serves crucial roles in protecting cells from oxidative stress. The present study investigated the regulatory effect of Prx V on glutamate‑induced effects on viability and apoptosis in HT22 cells. Western blotting was used for protein expression analysis and Annexin V/PI staining and flow cytometry for determination of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The activation of ERKs has been revealed to contribute to neuronal cell death in certain in vitro models of neurotoxicity. Persistent activation of ERK1/2 contributes to glutamate-induced oxidative toxicity (4245), which is consistent with the results of the present study. ERK also contributes to cell death through the suppression of anti-apoptotic signaling molecule RAC-α serine/threonine-protein kinase (34).…”
Section: Discussionsupporting
confidence: 93%
“…The activation of ERKs has been revealed to contribute to neuronal cell death in certain in vitro models of neurotoxicity. Persistent activation of ERK1/2 contributes to glutamate-induced oxidative toxicity (4245), which is consistent with the results of the present study. ERK also contributes to cell death through the suppression of anti-apoptotic signaling molecule RAC-α serine/threonine-protein kinase (34).…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that co-treatment with N-acetyl-L-cysteine (an intensive ROS scavenger) or MitoTEMPO (a mitochondrial ROS scavenger) downregulated Prx5 expression, indicating that the upregulation of Prx5 was related to glutamate-induced ROS generation (Figure 1(C)). These results are corresponded to previous study [18]. Since Prx5 is known to be broadly dispersed inside cells, including in the cytosol and mitochondria [19], we confirmed the subcellular distribution of Prx5 induced by glutamate using cytosolic and mitochondrial cell fractions.…”
Section: Glutamate Upregulated the Expression Level Of Cytprx5 And Mtsupporting
confidence: 92%
“…Of the six Prx subtypes, the antioxidant effect of Prx5 in various cellular systems has been well established. In previous studies, we reported that Prx5 reduces LPS-induced microglia activation and protects neuronal cells from neurotoxic substances, such as β-amyloid, iron, diethylhexyl phthalate, and glutamate [13,18,[30][31][32][33][34]. These findings highlight the necessity of further study on the relationship between the antioxidant effects and intracellular location of Prx5.…”
Section: Discussionmentioning
confidence: 80%
“…Prx V is an atypical 2-cys-Prx which is widely expressed in cellular compartments. It has been reported that Prx V is involved in cellular apoptosis induced by oxidative stress in various cells such as Hela cervical cancer cells and HT22 hippocampus cells through several pathways (29)(30)(31). The role of Prx V in the apoptosis of GC cells has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%